“You have to talk to those who were there (Utøya)…”: promoting children’s participation: a case of expert meetings and groups within the ombudsman in Norway - Musinguzi, Polycarp (2015)
The aim of this study was to investigate expert meetings and groups as a distinctive approach to promoting the participation of children and young people within the context of the children’s ombudsman in Norway. To achieve this broad objective, specific questions revolving around the rationale, character, significance and bottlenecks of expert meetings and groups were formulated. Premised on the findings of this investigation, the study would then draw implications for policy and practice within the field. A qualitative approach, in particular case study design was selected to facilitate collection of data and analysis of the resulting findings. This included collecting data about the case using in-depth / qualitative interviews and analyzing relevant documents. Coding and analysis of primary data drew inspiration from a constructivist grounded theory approach, while in analyzing secondary data, this approach was complemented with qualitative content analysis. The entire coding and analysis procedure was facilitated by NVivo’s powerful analytical tools. In general, the choice of a qualitative approaches for this study was informed by their ability to deliver a thick understanding of the research phenomena, and describe the findings giving due consideration to the relevance of the context The findings of this investigation have revealed that expert meetings and groups have a clear premise; essentially as a fulfillment of children’s fundamental and democratic right to actively participate in society as competent citizens, in accordance with evolving capacities. At the same time, these initiatives are intended to provide a powerful empowerment force through which to underscore the plight of children, so that predominantly adult run systems can take conscious child sensitive precautions, both those required to alleviate present indignity, and prevent future reoccurrences. The study observes that the character of expert meetings and groups celebrates a firm grounding in the basic principles required for achieving an effective and ethical participatory ethos. The findings further point to an array of individual, organizational and wider system benefits accruing from these initiatives. Outstanding benefits include; providing a platform for the realization of children’s rights, propelling active empowerment for participants, and learning outcomes for adults; while consciously challenging the system to effect quality and more child friendly services. Amidst such gains, the ombudsman acknowledges that the promise of participation lies in the power to inculcate within society an all-round value system; that both celebrates children’s competency, and demonstrates genuine commitment to engage with them respectfully as equals. Such a model of participation should not be restrictively interpreted in view of tokenistic information giving and collaborative engagement; when the fundamental premises for according children and young people an equal opportunity to influence the agenda for consultation or other forms of participation largely remain an adult monopoly. Even more pertinent is that participation should not be constructed as a magic wand wielded by adults to exterminate problems in particular situations where the wellbeing of children is threatened. To the contrary, participation must be visibly seen, felt and robustly encouraged in natural settings within which both adults and children are in constant interaction. It must be a norm which all children everywhere can experience for a right, anytime, anywhere. Nevertheless, practical realization of a participatory ethos of this nature in many contexts presents real, conflicting and daunting dilemmas with which both children and adults must collaboratively grapple. In conclusion, this study draws on the pool of benefits reported, to argue the case for establishing independent national human rights institutions for children; and for concerted efforts among duty bearers to develop pragmatic solutions for realizing their participation rights within the diversity of natural settings. This study raises the question on possible mechanisms and responsibility centres to follow-up on the uptake and redress of recommendations by the ombudsman, ensuing from expert meetings and groups. A complementary question is how to achieve a participatory culture described above. Satisfying these dilemmas lay outside the scope of this study, but will nevertheless be important for maintaining the institution’s relevance as a credible voice and watchdog for children’s rights. More importantly, it is a question to which children everywhere merit valid, honest, quick, respectful and uncensored accountability from across civilizations world over.